025 Management and outcomes of febrile infants. (14th September 2011) - Hare, M; Burke, D; Rimmer, C
Abstract : Objectives and Background: One of the new Emergency Department (ED) clinical quality indicators (CQIs) defines febrile infants as "high risk" patients requiring consultant "sign-off" prior to discharge. A service evaluation of the management and outcomes of febrile infants attending our ED in 2010 was undertaken in order to determine how our department would have complied with this CQI. Methods: The sample population was identified and data collected retrospectively using the department's electronic database. Of those, 100 patients discharged but not initially seen by a consultant were randomly selected and had their case notes reviewed. Results: 1137 febrile infants attended the ED and 8% were re-attendances (Abstract 025 figure 1 ). 75% attended outside of normal working hours, of which 22% attended at night, when a consultant is not routinely on site (Abstract 025 figure 2 ). 78% of the infants were discharged, 22% were admitted, and only an estimated 6% of those discharged were "signed-off" by a consultant. The majority of febrile infants were seen by an SHO (Abstract 025 figure 3 ). 2.5% were well, 93% had a minor illness, 3.6% had a serious illness and in 0.9% the diagnosis was unknown. None of the patients died. Conclusion: Febrile infants represent a significant proportion of our ED attendances (2.5%). A high proportion of febrile infants re-attend, and few are signed off by a consultant prior to discharge. The majority of febrile infants have minor illnesses. This service evaluation would suggest that the threshold for defining high-risk should be reviewed, possibly to include other clinical signs/symptoms in the definition, or to reduce the defined age to <6 months. Otherwise significant changes to ED consultant working patterns are likely to be required in order to increase the number of patients in this high-risk group achieving consultant "sign-off".